Porous PVDF as effective sonic wave driven nanogenerators. - Cha, S; Kim, S; Kim, H; Ku, J; Sohn, J; Park, Y; Song, BG; Jung, M; Lee, E; Choi, B; Park, J; Wang, Z; et al. (2011)
Piezomaterials are known to display enhanced energy conversion efficiency at nanoscale due to geometrical effect and improved mechanical properties. Although piezoelectric nanowires have been the most widely and dominantly researched structure for this application, there only exist a limited number of piezomaterials that can be easily manufactured into nanowires, thus, developing effective and reliable means of preparing nanostructures from a wide variety of piezomaterials is essential for the advancement of self-powered nanotechnology. In this study, we present nanoporous arrays of polyvinylidene fluoride (PVDF), fabricated by a lithography-free, template-assisted preparation method, as an effective alternative to nanowires for robust piezoelectric nanogenerators. We further demonstrate that our porous PVDF nanogenerators produce the rectified power density of 0.17 mW/cm3 with the piezoelectric potential and the piezoelectric current enhanced to be 5.2 times and 6 times those from bulk PVDF film nanogenerators under the same sonic-input.